Investigation of the effects of 3D printing parameters on mechanical tests of PLA parts produced by MEX 3D printing using Taguchi method - Özgür Verim; Omar Saeed; Mohamed Hamdy Eid; Samy F. Mahmoud; Dalia I. Saleh; Abdallah Elshawadfy Elwakeel (Scientific Reports)
Abstract With the widespread use of the Material Extrusion method in the 3D printing industry, it has become important to determine the optimum printing parameters to improve the mechanical characteristics of Polylactic Acid material according to the place of use. It is important to choose the right press parameters according to the forces to which the material is subjected. In research, we examined the impacts of 3D printing parameters such as Layer Thickness, Infill Density, Raster Angle, Printing Speed, and Wall Thickness on mechanical tests covering tensile, compression, flexural, impact, hardness, and surface roughness. We employed Taguchi analysis to streamline the number of experiments and determine the optimal printing parameters to maximize mechanical performance. Five samples were determined for each experimental design measurement. According to the results of the research, Layer Thickness and Infill Density parameters were found to be very important parameters in mechanical tests according to the effect and contribution ratios. The effect ranking of the Infill Density parameter on tensile, compressive and impact strength was the best (1) and the contribution rate was the highest (55.21%, 80.86% and 63.61%). In flexural strength, the order of effect and contribution rate (25.66%) were found in the 2nd place. The effect of Layer Thickness parameter on impact, hardness and surface roughness tests was found to be significant (2,1 and 1). The effect values in tensile and compression tests were also found to be moderate (3). Considering the efficiency levels and contribution rates for the other parameters, the order of importance can be listed as Wall Thickness, Raster Angle and Printing Speed. With the help of this study, the importance levels of the parameters during the formation of parts under combined forces were determined and presented to the literature.